A Contemporary Review of Hate Crime Legislation in the United States - Bills, Matthew A. (Criminal justice policy review, 2023)
Hate-motivated crime remains problematic in the United States. California passed the first hate crime law in 1978; Congress followed in 1990. States continue to amend their hate crime legislation, producing an amalgam of statutory provisions. This article creates a conceptual framework from which to classify hate crime legislation across the 50 states and Washington, DC. Laws were identified through Westlaw. Analyses compared the types of crimes covered, discrete and insular minorities protected, prosecutorial alternatives, mandates for law enforcement agencies, and additional rights provided to victims among states’ legislation. Considerable variation in scope and content of hate crime legislation exists among states, leaving several vulnerable groups unprotected, law enforcement underprepared, and victim rights and resources sparse. Future directions for hate crime policy and legislation are discussed.